2012
DOI: 10.1007/s10592-012-0348-8
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics of the endangered Dorcas gazelle (Gazella dorcas spp.) in Northwestern Africa

Abstract: Large mammals are seriously threatened in North Africa, with emblematic cases of extinction reported during the twentieth century. The Dorcas gazelle (Gazella dorcas) is an endangered species whose populations drastically declined in the last few decades. In this work we applied both invasive and non-invasive molecular methods to document for the first time patterns of genetic diversity and population structure of G. dorcas in its northwestern range, using 13 microsatellite loci and a 716 bp fragment of mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…However, most studies have focused on smallsized, non-volant vertebrates with relatively low dispersal capacity (Boratyński et al 2012;Dobigny et al 2013;Guiller et al 2001;Metallinou et al 2012;Sousa et al 2011), while still very little is known about larger and more vagile species, for which barrier effects may be less pronounced. Of the few existing studies on large and medium size mammals, some show very little to no genetic structure (Bärmann et al 2013;Gaubert et al 2012;Lerp et al 2011), while others exhibit distinct mitochondrial lineages that co-occur throughout North Africa (Gaubert et al 2009(Gaubert et al , 2011Godinho et al 2012;Trucchi and Sbordoni 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies have focused on smallsized, non-volant vertebrates with relatively low dispersal capacity (Boratyński et al 2012;Dobigny et al 2013;Guiller et al 2001;Metallinou et al 2012;Sousa et al 2011), while still very little is known about larger and more vagile species, for which barrier effects may be less pronounced. Of the few existing studies on large and medium size mammals, some show very little to no genetic structure (Bärmann et al 2013;Gaubert et al 2012;Lerp et al 2011), while others exhibit distinct mitochondrial lineages that co-occur throughout North Africa (Gaubert et al 2009(Gaubert et al , 2011Godinho et al 2012;Trucchi and Sbordoni 2009).…”
Section: Introductionmentioning
confidence: 99%
“…; Godinho et al. ) even though they could be poor predictors of genetic diversity in many population scenarios (Hansson and Westerberg ).…”
Section: Introductionmentioning
confidence: 99%
“…Lerp et al . () showed that there is no evidence for geographical subspecies within G. dorcas Linnaeus, 1758, except that G. saudiya Carruthers and Schwartz, 1936, G. d. pelzelni Kohl, 1886, and G. d. massaesyla Cabrera, 1928 might form distinct (sub)species as they seem to comprise monophyletic groups within G. dorcas (Hammond et al ., ; Lerp et al ., ; Godinho et al ., ). To evaluate the new taxonomy by Groves & Grubb () and to reconstruct the phylogeny of the genus Gazella , studies like these are needed for other gazelle species as well.…”
Section: Introductionmentioning
confidence: 97%
“…In the last decade, several such studies have been conducted on gazelles: Wacher et al (2011) and Hassanin et al (2012) have confirmed that G. marica Thomas, 1897 and G. subgutturosa are two separate species; and Wronski et al (2010) and Lerp et al (2013) found two reciprocally monophyletic clades within G. gazella that could be treated as distinct species. Lerp et al (2011) showed that there is no evidence for geographical subspecies within G. dorcas Linnaeus, 1758, except that G. saudiya Carruthers and Schwartz, 1936, G. d. pelzelni Kohl, 1886, and G. d. massaesyla Cabrera, 1928 might form distinct (sub)species as they seem to comprise monophyletic groups within G. dorcas (Hammond et al, 2000;Lerp et al, 2011;Godinho et al, 2012). To evaluate the new taxonomy by Groves & Grubb (2011) and to reconstruct the phylogeny of the genus Gazella, studies like these are needed for other gazelle species as well.…”
Section: Introductionmentioning
confidence: 99%